Pengaruh Pendidikan Kewirausahaan dan Pengembangan Soft Skill terhadap Intensi Berwirausaha Mahasiswa - Cheresentia Situmorang; Dian Pasaribu; Fais Irawan; Rejosu Vanhot Sianturi; Shesy Eightia Tinambunan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the influence of entrepreneurship education and soft skills development on the entrepreneurial intentions of Economics Education students at Universitas Negeri Medan. Based on a survey of 41 respondents and a multiple linear regression analysis, it was found that both variables significantly influence students' entrepreneurial intentions. The results show that entrepreneurship education (with a t-value of 2.406) and soft skills (with a t-value of 3.844) have a positive impact. Collectively, these two factors can explain 71.4% of the variation in entrepreneurial intention. The regression model obtained is Y = 2.251 + 0.371X1 + 0.601X2. The conclusion of this research confirms the importance of integrating entrepreneurship education and soft skills development to increase entrepreneurial intention and support economic development.